Modeling wireless sensor networks using a collaborative graph-based model - Rodríguez Peralta, Laura M. (2022)
: In several application scenarios, like the case of structural monitoring, it is important to model and represent the Wireless Sensor Networks (WSN) to be deployed. To model the components and properties of entire WSN types of collaboration in WSNs, we have created the Collaborative Wireless Sensor Networks (CWSN) model. This model also models the different types of collaboration that occur in a WSN. Our main goal is to provide a theoretical mathematical foundation that can model and analyze WSNs. Our approach is based on graph theory and propositional logic. The main contribution of this paper is applying the CWSN model to describe and represent a WSN. The use of the CWSN model brings several advantages, such as enabling the graphical representation of the state of the network and of several important properties: 1) the network topology; 2) the transmission between nodes considering a multi-hop communication; 3) the transmission hierarchy; 4) the evolution of the networks through a succession of graphs; and so on. Copyright © 2015 IFSA Publishing, S. L